2014
DOI: 10.1080/10511482.2013.852603
|View full text |Cite
|
Sign up to set email alerts
|

Leaving Homelessness Behind: Housing Decisions Among Families Exiting Shelter

Abstract: Because homelessness assistance programs are designed to help families, it is important for policymakers and practitioners to understand how families experiencing homelessness make housing decisions, particularly when they decide not to use available services. This study explores those decisions using in-depth qualitative interviews with 80 families recruited in shelters across four sites approximately six months after they were assigned to one of four conditions (permanent housing subsidies, project-based tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 30 publications
1
51
0
1
Order By: Relevance
“…Several studies have found housing choice to be positively related to housing satisfaction (Nelson, Hall, & Forchuk, ; Srebnik, Livingston, Gordon, & King, ; City of Toronto Shelter, Support & Housing Administration, ; Yanos, Barrow, & Tsemberis, ), residential stability (Srebnik et al., ), subjective quality of life (Nelson et al., ), and other key outcomes (Collins, Clifasefi, Andrasik, et al., ). No matter what the population, if the “best” immediate secure housing option still requires considerable compromise on key needs–as explored in a qualitative study exploring family rehousing across the United States–a likely result is continuous cycling through unsatisfactory housing situations (Fisher et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found housing choice to be positively related to housing satisfaction (Nelson, Hall, & Forchuk, ; Srebnik, Livingston, Gordon, & King, ; City of Toronto Shelter, Support & Housing Administration, ; Yanos, Barrow, & Tsemberis, ), residential stability (Srebnik et al., ), subjective quality of life (Nelson et al., ), and other key outcomes (Collins, Clifasefi, Andrasik, et al., ). No matter what the population, if the “best” immediate secure housing option still requires considerable compromise on key needs–as explored in a qualitative study exploring family rehousing across the United States–a likely result is continuous cycling through unsatisfactory housing situations (Fisher et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research also provides affected individuals the opportunity to contribute their voice to program and policy discussions. Whereas there is a body of literature of individuals’ experiences of homelessness and HF (Anucha, ; Collins, Clifasefi, Andrasik, et al., ; Collins, Clifasefi, Dana, et al., ; Lincoln, Plachta‐Elliott, & Espejo, ; Padgett, Gulcur, & Tsemberis, ), as well as relevant qualitative studies that detail rehousing experiences among homeless families (Fisher, Mayberry, Shinn, & Khadduri, ), no qualitative studies to date have focused exclusively on factors that may influence housing stability or housing disruption among chronically homeless individuals with severe alcohol problems.…”
mentioning
confidence: 99%
“…A separate multi-site study sponsored by U.S. Department of Housing and Urban Development (HUD) used an experimental design to compare housing, health and other outcomes of homeless families who receive rapid re-housing, transitional housing, a permanent housing subsidy or emergency shelter placement (U.S. Department of Housing and Urban Development, 2013a). A recent peer-reviewed study used data from qualitative interviews to examine the housing decisions of families participating in that study (Fisher, Mayberry, Shinn, & Khadduri, 2014), but quantitative results on the relative effectiveness of the interventions studied have not yet been published. Beyond these two studies, the body of evidence on the outcomes of households served by homelessness prevention and rapid re-housing programs is limited primarily to less rigorous, non-peer reviewed evaluations conducted in a number of individual communities that track returns to homeless among those receiving prevention and rapid re-housing services (see for example : Burt, Pearson, & Montgomery, 2005;Connecticut Coalition to End Homelessness, 2013;Rodriguez, 2013;Taylor, 2014;Wong, Koppel, & Culhane, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Homeless and previously homeless population is highly stigmatized, often stereotyped by an association with violence (Fisher, Mayberry, Shinn, & Khadduri, 2014;Sard & Rice 2014;Cunningham, Gillespie & Anderson, 2015). In addition to safety concerns for the health care workers delivering patient care, other environmental factors can exacerbate this concern.…”
Section: Safety Concerns Involving Hud-vash Recipientsmentioning
confidence: 99%
“…In addition to safety concerns for the health care workers delivering patient care, other environmental factors can exacerbate this concern. In their efforts to secure permanent housing, homeless individuals are more likely to find housing in neighborhoods experiencing social ills involving violence and illegal drug use (Cunningham, Gillespie & Anderson, 2015;Fisher et al, 2014;Sard & Rice 2014). This, in turn, can have an impact on health care workers' sense of security, and some staff may refuse to provide services in high crime areas or require an escort.…”
Section: Safety Concerns Involving Hud-vash Recipientsmentioning
confidence: 99%